SOLVING SOME ISSUES RELATED TO PLATO POLYGRAPHY DESIGN IN COMPUTER GRAPHICS - SH. Abdurahmonov,; V. Zokirov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In a scientific article called “Solving some problems on the design of Platonic solids on a computer graph”, the processes of solving some problems on the design of regular polyhedral on a computer graph are described.